A theorem about snakes for weak Cartesian systems - Davydov, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
It is shown that Karlin's theorem about snakes remains true for polynomials in any weak Cartesian system of continuous functions on a compact set without any change in the statement, and the existence part is valid for arbitrary weak Chebyshev systems.